District-Level Health Management and Health System Performance: The Ethiopia Primary Healthcare Transformation Initiative - Lingrui Liu; Mayur M. Desai; Netsanet Fetene; Temsgen Ayehu; Kidest Nadew; Erika Linnander (Kerman University of Medical Sciences, 2022)
BackgroundDespite a wide range of interventions to improve district health management capacity in low-income settings, evidence of the impact of these investments on system-wide management capacity and primary healthcare systems performance is limited. To address this gap, we conducted a longitudinal study of the 36 rural districts (woredas), including 229 health centers, participating in the Primary Healthcare Transformation Initiative (PTI) in Ethiopia. MethodsBetween 2015 and 2017, we collected quantitative measures of management capacity at the district and health center levels and a primary healthcare key performance indicator (KPI) summary score based on antenatal care (ANC) coverage, contraception use, skilled birth attendance, infant immunization, and availability of essential medications. We conducted repeated measures analysis of variance (ANOVA) to assess (1) changes in management capacities at the district health office level and health center level, (2) changes in health systems performance, and (3) the differential effects of more vs less intensive intervention models. ResultsAdherence to management standards at both district and health center levels improved during the intervention, and the most prominent improvement was achieved during district managers' exposure to intensive mentorship and education. We did not observe similar patterns of change in KPI summary score. ConclusionThe district health office is a valuable entry point for primary healthcare reform, and district- and facility-level management capacity can be measured and improved in a relatively short period of time. A combination of intensive mentorship and structured team-based education can serve as boh an accelerator for change and a mechanism to inform broader reform efforts.